Parents' Attitudes toward Oral Rehydration Therapy in Children with Mild-to-Moderate Dehydration. (4th November 2013) - Nir, Vered; Nadir, Erez; Schechter, Yaffa; Kline-Kremer, Adi
Abstract : Objective . According to current guidelines, the first line of treatment for mild-to-moderate dehydration is oral rehydration; the second line is rehydration through a nasogastric tube. Both methods are widely underused. This study was conducted to evaluate parents' attitudes towards rehydration methods used in pediatric emergency departments. Design . 100 questionnaires were distributed to parents of children who visited emergency room due to gastroenteritis and suspected dehydration. Results . 75 of the parents expected their child to get IV fluids. 49 of them would refuse to consider oral rehydration. 75 of the parents would refuse to consider insertion of nasogastric tube. Parents whose children were previously treated intravenously tended to be less likely to agree to oral treatment. Parents were more prone to decline oral rehydration if the main measurement of dehydration was the child's clinical appearance, clinical appearance with vomiting, or child's refusal to drink and were more likely to agree if the main measurement was diarrhea, diarrhea with clinical appearance, or clinical personnel opinion. Conclusions . This is the first study to examine parents' expectations. We found that in the majority of cases, parents' expectations contradict current guidelines. Efforts should be taken to educate parents in order to allow full implementation of the guidelines.